Case report: Long-lasting SARS-CoV-2 infection with post-COVID-19 condition in two patients with chronic lymphocytic leukemia: The emerging therapeutic role of casirivimab/imdevimab - Ballotta, Laura; Simonetti, Omar; D’Agaro, Pierlanfranco; Segat, Ludovica; Koncan, Raffaella; Martinez-Orellana, Pamela; Dattola, Federica; Orsini, Emanuele; Marcello, Alessandro; Dal Monego, Simeone; Licastro, Danilo; Misin, Andrea; et al. (Frontiers in Oncology, 2022)
Post Coronavirus Disease 2019 (post COVID-19) condition, previously referred to as long COVID, in-cludes a post-acute syndrome defined by the presence of non-specific symptoms occuring usually 3 months from the onset of the acute phase and lasting at least 2 months. Patients with chronic lymphocytic leukemia (CLL) represent a high-risk population for COVID-19. Moreover, the response to SARS-CoV-2 vaccination is often absent or inadequate. The introduction of monoclonal antibo-dies (Mabs) in the treatment landscape of COVID-19 allowed to reduce hospitalization and mortali-ty in mild-moderate SARS-CoV-2 infection, but limited data are available in hematological patients. We here report the effective use of Casirivimab/Imdevimab (CI) in the treatment of two CLL pa-tients with persistent infection and post COVID-19 condition. Full-genome sequencing of viral RNA from nasopharyngeal swabs was performed at the time of COVID-19 diagnosis and before the ad-ministration of CI. Both patients experienced persistent SARS-CoV-2 infection with no seroconver-sion for 8 and 7 months respectively, associated with COVID symptoms. In both cases after the in-fusion of CI we observed a rapid negativization of the nasal swabs, the resolution of post COVID-19 condition and the development of both IgG against trimeric spike protein and receptor-binding domain (RBD) of the spike protein. The analysis of viral genome in the period elapsed from the ti-me of COVID-19 diagnosis and the administration of Mabs showed the development of new muta-tions, especially in the S gene. The genome variations observed during time suggest a role of persi-stent SARS-CoV-2 infection as a possible source for the development of viral variants. The effects observed in these 2 patients appeared strongly related with passive immunity conferred by CI treatment permitting SARS-CoV-2 clearance and resolution of post COVID-19 condition. On these grounds, passive anti SARS-CoV-2 antibody treatment may represent in some patients with persi-stent SARS-CoV-2 infection a possible therapeutic option.